Analisis Faktor-Faktor yang Memengaruhi Brand trust dan Purchase Intention: (Studi pada Konsumen Tumbler Premium di Wilayah DKI Jakarta) - Fathin Aliaa Hamdi; Usep Suhud; Meta Bara Berutu (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to find out the relationship between e-WOM to purchase intention, e-WOM to brand trust, brand image to purchase intention, brand image to brand trust, social media marketing to purchase intention, social media marketing to brand trust, and brand trust to purchase intention. This study used a purposive sampling technique to gather 240 samples from Corkcicle users in DKI Jakarta who were between the ages of 20 and 50. The results of this study indicate that six hypotheses are accepted, namely e-WOM has a positive and significant effect on brand trust, e-WOM has a positive and significant effect on brand trust, brand image has a positive and significant effect on purchase intention, brand image has a positive and significant effect on brand trust, social media marketing has a positive and significant effect on purchase intention, and brand trust has a positive and significant effect on purchase intention. However, one hypothesis is rejected, social media marketing is proven to have a negative and insignificant effect on brand trust.